(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Solar cooking is popular in India and many other developing nations where LPG, coal, and other fossil fuels are scarce. A solar cooking system with or without temporary heat storage has been designed and deployed in a number of nations across the globe. Cooking necessitates the use of thermal energy, which is presently supplied by liquefied petroleum gas, kerosene, and coal, all of which are costly fuels. As a source of heat, solar energy may also be utilized to prepare food. Solar energy is accessible nearly everywhere. To effectively prepare meals, a solar energy-stored cooker is utilized. The solar energy storage cooker is intended for both cooking and storing thermal energy. When heat energy is stored, the oven’s efficiency and utility are improved when sunshine is not available. This kind of cooking oven is long-lasting, low-cost, and effective, making it suitable for every household. This article provides an in-depth examination of the solar energy storage cooker and how it may be used in today’s society. Despite the fact that many studies in this area have been performed in the past, additional study in this field is urgently needed in the future.